Occupational exposure to poultry and prevalence of antibodies against Marek's disease virus and avian leukosis retroviruses. Issue 6 (June 1996) - Choudat, D; Dambrine, G; Delemotte, B; Coudert, F
Abstract : OBJECTIVES: To compare the prevalence of antibodies against Marek's disease herpes virus (MDV) and against avian leukosis viruses type C (ALV) in groups of workers exposed to poultry and in unexposed groups. METHODS: Antibodies directed against avian viral proteins were detected by enzyme linked immunosorbent assay in 549 subjects. Exposure to chickens was high in two subgroups: farmers on intensive chicken farms and workers at chicken slaughterhouses. One subgroup, traditional farmers on dairy or pig farms with poultry, had moderate exposure to poultry. Another subgroup, farmers and slaughterhouse workers on quail farms, had high exposure to quails. Three subgroups were not exposed to chickens: farmers on dairy or pig farms without poultry, workers at cattle slaughterhouses, and white collar workers. Also, MDV antibodies were tested after serum sample adsorption with chicken antigens in 134 serum samples. RESULTS: The prevalence of antibodies against MDV was significantly higher in the exposed subgroups than in unexposed groups (odds ratio (OR) 6.17; 95% confidence interval (95% CI) 3.91-9.75). No association was found between seroprevalence and age. However, higher prevalence was found among women and was related to duration of exposure to chickens. The concentration of antibodies from a few subjects remained very high after adsorption. Significant differences between the men and women were found for the prevalence of antibodies for ALV but were not related to exposure to chickens. CONCLUSIONS: The prevalence of antibodies against MDV was significantly higher among workers exposed to chickens and was related to sex and duration of exposure. The higher prevalence of antibodies against avian oncogenic viruses found among women compared with men may be induced by differences in exposure or by genetic factors. The meaning of these high titres could be related to the presence of MDV in humans. Because the involvement of animal oncogenic viruses in human cancer is indicated by epidemiological and some experimental studies, the integration of viral DNA in human cells needs to be investigated.